Árukapcsolás és csomagban történő értékesítés: Jogesetek és közgazdasági elmélet - Pál Valentiny (Hungarian Academy of Sciences, Institute of Economics, 2011)
– Economists and lawyers are badly divided on issues concerning tying and bundling. Permissivie and prohibitive attitudes are changing radically in the literature and in the legal practice. After a short discurse on the notions, we introduce the basic ideas, theories and debates according to schools in economics and market structures. Based on relevant cases of the US and EU we finally summarize the changes in economic theory and their impact on the rule of reason in these cases.
Keywords: K21; L12; L21; 330; tying; bundling; antitrust; competition policy; economic theory; cases; Leistungsbündel; Wirtschaftstheorie